Intravenous Administration of Human Umbilical Cord Blood‐Derived AC133+ Endothelial Progenitor Cells in Rat Stroke Model Reduces Infarct Volume: Magnetic Resonance Imaging and Histological Findings. (9th August 2013) - Iskander, Asm; Knight, Robert A.; Zhang, Zheng Gang; Ewing, James R.; Shankar, Adarsh; Varma, Nadimpalli Ravi S.; Bagher-Ebadian, Hassan; Ali, Meser M.; Arbab, Ali S.; Janic, Branislava
Abstract : This study examined the effect of AC133+ endothelial progenitor cells derived from human umbilical cord blood on stroke development and resolution in a middle cerebral artery occlusion rat model. It was found that transplanted cells selectively migrated to the ischemic brain parenchyma, where they exerted a therapeutic effect on the extent of tissue damage, regeneration, and time course of stroke resolution. Abstract : Endothelial progenitor cells (EPCs) hold enormous therapeutic potential for ischemic vascular diseases. Previous studies have indicated that stem/progenitor cells derived from human umbilical cord blood (hUCB) improve functional recovery in stroke models. Here, we examined the effect of hUCB AC133+ EPCs on stroke development and resolution in a middle cerebral artery occlusion (MCAo) rat model. Since the success of cell therapies strongly depends on the ability to monitor in vivo the migration of transplanted cells, we also assessed the capacity of magnetic resonance imaging (MRI) to track in vivo the magnetically labeled cells that were administered. Animals were subjected to transient MCAo and 24 hours later injected intravenously with 10 7 hUCB AC133+ EPCs. MRI performed at days 1, 7, and 14 after the insult showed accumulation of transplanted cells in stroke‐affected hemispheres and revealed that stroke volume decreased at a significantly higher rate in cell‐treated animals. Immunohistochemistry analysis of brain tissues localized the administered cells in the stroke‐affected hemispheres only and indicated that these cells may have significantly affected the magnitude of endogenous proliferation, angiogenesis, and neurogenesis. We conclude that transplanted cells selectively migrated to the ischemic brain parenchyma, where they exerted a therapeutic effect on the extent of tissue damage, regeneration, and time course of stroke resolution.